Growth, poverty and inequality in Rwanda: A broad perspective - Marijke Verpoorten (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This study focuses on growth, poverty and inequality in Rwanda. We take a broad perspective, in two respects. First, we consider a long time period so as to compare the current situation with the pre-war situation, allowing us to assess whether the recent successes can be attributed to a recovery from a very low post-war base or whether they mark 'real' progress. Second, we look beyond static measures of material welfare and study economic and social mobility as well as indicators of human development and subjective well-being.
Keywords: O12; O15; 330; Rwanda; poverty; inequality; mobility; happiness